2017
DOI: 10.1136/bmjopen-2017-016557
|View full text |Cite
|
Sign up to set email alerts
|

Association between socio-economic status and dental caries in elderly people in Sichuan Province, China: a cross-sectional study

Abstract: ObjectivesAs a vulnerable group, the elders’ oral health gained less attention, particularly the relationship between socioeconomic status (SES) and dental caries. This study aimed to assess the associations and to explore the effects of confounders on the associations in elderly people.DesignCross-sectional study.Settings3 neighbourhood committees and 3 village committees in Sichuan Province, China.Participants744 people (362 men and 382 women) aged 65–74 years were included.Outcome measuresOral health outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
6
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 41 publications
2
39
6
6
Order By: Relevance
“…Although many previous studies have reported a negative correlation between education level and caries, a statistically significant correlation was not detected in this study [31]. This may be due to the generally low education level among the participants.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although many previous studies have reported a negative correlation between education level and caries, a statistically significant correlation was not detected in this study [31]. This may be due to the generally low education level among the participants.…”
Section: Discussioncontrasting
confidence: 99%
“…Some socio-demographic factors, such as ethnicity and annual household income, are usually defined as risk factors for dental caries [31,33]. In this study, these influence on dental caries experience was less than geographic variable.…”
Section: Discussionmentioning
confidence: 68%
“…Although many previous studies have reported a negative correlation between education level and caries, a statistically signi cant correlation was not detected in this study [35]. This may be due to the generally low education level among the participants.…”
Section: Discussioncontrasting
confidence: 97%
“…In another cross-sectional study in 2017 which sought to determine the association between SES and dental caries in elderly people in Sichuan Province, China, the burden associated with dental caries remained high in disadvantaged, poor and older populations 15 . In addition, a systematic review and meta-analysis study in 2015 which explored socioeconomic inequality and dental caries found that those with lower educational level or lower income, were most likely to have a higher risk of caries lesions 16 .…”
Section: Introductionmentioning
confidence: 99%